Customer involvement capability and service firm performance: The mediating role of innovation - Anning-Dorson, T. (Journal of Business Research, 2018)
This study contributes to the literature on customer involvement by assessing the influence firm-level customer involvement capability has on service firm performance in two economic contexts. The study further examines innovation as a necessary mediator between customer involvement capability and firm performance. Data collected from service firms operating in two countries, the United Kingdom and Ghana, is analysed and used to validate the article's theoretical and empirical contributions. The results show that customer involvement cap ability has a positive and direct relationship with service firm performance in Ghana but a negative and direct relationship in the British context. The implication is that the effect of firm-level capability can be context specific and that its development must therefore be aligned with the context in which a firm operates. On the other hand, it was found that in both contexts, innovation (product and process) mediated the relationship between involvement capability and firm performance.
Research Article
Keywords: Customer involvement; Innovation; Emerging markets; United Kingdom; Ghana